Identification of Lactobacillus plantarum in Breast Milk - Mansoureh Taghizadeh; Hajieh Ghasemian Safaei; Farkhondeh Poursina (Research in Molecular Medicine, 2017)
Backgrounds : The role of potentially probiotic lactic acid bacteria of human milk   in  the  early  colonization and protection of infant against infections is the subject of increasing researches. Colonization with Lactobacillus plantarum in early infancy is suggested to be important for health in later life. However, we presently investigated the strain of Lactobacillus plantarum in the breast  milk  among Iranian infants.   Materials and Methods: Human breast milk samples (n = 40) with all full‑term breastfed were collected from randomly lactating women. Information about personal characteristics were collected after birth. The samples were cultured in media through Pour plate with MRS (de Man, Rogosa and Sharpe) (Merck Germany) and were detected by biochemical methods. Then, the genus of Lactobacillus was identified using 16-23S rRNA and In order to identify L. plantarum species, the recA gene primer in PCR method was done. Results: Our study showed 35 (87.5%) as suspected of Lactobacilli based on phenotypic tests and 30 (85.71%) were confirmed as Lactobacillus genus using genotypic PCR method all of whom were Lactobacillus plantarum. Conclusion: The probiotic bacteria in mother’s breast milk could have positive effects on her infants health, and therefore, would open new perspectives on using breast milk as a  source of probiotic bacteria for bacteriotherapy.